Driving energy transition in BRI nations: The role of education, globalization, trade liberalization, and financial deepening – A comprehensive linear and nonlinear approach - Md Qamaruzzaman (Energy Strategy Reviews)
This study investigates the drivers of energy transition among Belt and Road Initiative (BRI) countries, focusing on the roles of education, globalization, trade openness, and financial development. With the shift toward sustainable energy as a global priority, understanding these influences within BRI nations is crucial to formulating effective policies for renewable energy adoption. Using panel data from 46 BRI countries spanning 2000–2021, we employ advanced econometric techniques, including the Continuously Updated Fully Modified (CUP-FM) and Continuously Updated Bias-Corrected (CUP-BC) models, to assess both linear and nonlinear effects. Results show that education significantly promotes renewable energy by fostering skills and environmental awareness. Globalization and trade openness also support energy transition by facilitating the exchange of green technologies and sustainable practices, while financial development enables investment in renewable infrastructure. This research fills a notable gap in energy transition literature, providing evidence from diverse economic contexts and offering actionable insights for policymakers. We recommend prioritizing investment in education to enhance awareness, fostering international cooperation to facilitate technology transfer, and developing robust financial systems to support renewable energy projects. These strategies are essential for advancing the energy transition and achieving climate goals within BRI nations.